HUMAN CAPITAL DEVELOPMENT - GUARANTEE OF PERSONAL-SOCIAL-STATE DEVELOPMENT (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article talks about the development of societies and states, and the economic well-being of peoples directly depends on human capital. It has been analyzed that countries that do not pay enough attention to the development of human capital, no matter how many rich natural resources they have, will still lag behind in development. In the development of human capital, the need for reforms in the fields of education, especially adult education, health care, and social protection was explained. The initial results of the fundamental changes carried out in this regard in New Uzbekistan have been recorded.